2003
DOI: 10.1002/jnr.10728
|View full text |Cite
|
Sign up to set email alerts
|

Role for M5 muscarinic acetylcholine receptors in cocaine addiction

Abstract: Muscarinic cholinergic receptors of the M5 subtype are expressed by dopamine-containing neurons of the ventral tegmentum. These M5 receptors modulate the activity of midbrain dopaminergic neurons, which play an important role in mediating reinforcing properties of abused psychostimulants like cocaine. The potential role of M5 receptors in the reinforcing effects of cocaine was investigated using M5 receptor-deficient mice in a model of acute cocaine self-administration. The M5-deficient mice self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 25 publications
(41 reference statements)
12
88
1
4
Order By: Relevance
“…Conversely, lesions of the pedunculopontine nucleus (a source of ACh to the VTA) inhibit the development of CPP to morphine and amphetamine (Bechara and van der Kooy, 1989;Olmstead and Franklin, 1993). M 5 À/À rodents also spend less time in a cocaine-paired compartment during a CPP procedure compared to wild-type rodents (Fink-Jensen et al, 2003). Consistent with the positive association of VTA ACh with reward, increasing both muscarinic and nicotinic cholinergic VTA activity appears to heighten CPP to drugs of abuse.…”
Section: Acetylcholine and Conditioned Learningmentioning
confidence: 88%
See 3 more Smart Citations
“…Conversely, lesions of the pedunculopontine nucleus (a source of ACh to the VTA) inhibit the development of CPP to morphine and amphetamine (Bechara and van der Kooy, 1989;Olmstead and Franklin, 1993). M 5 À/À rodents also spend less time in a cocaine-paired compartment during a CPP procedure compared to wild-type rodents (Fink-Jensen et al, 2003). Consistent with the positive association of VTA ACh with reward, increasing both muscarinic and nicotinic cholinergic VTA activity appears to heighten CPP to drugs of abuse.…”
Section: Acetylcholine and Conditioned Learningmentioning
confidence: 88%
“…In FR models, animals increase their rate of self-administration as the unit dose of a drug is decreased (to compensate for decreases in the unit dose) and reduce responding as the unit dose is increased (Arnold and Roberts, 1997;Koob, 2000). Progressive ratio schedules are used to evaluate the reinforcing efficacy of a selfadministered drug by increasing the response requirements for each successive reinforcement and determining the (Ikemoto and Wise, 2002;Redgrave and Horrell, 1976) Rewarding effect of cocaine mediated through M 5 receptors (Fink-Jensen et al, 2003;Thomsen et al, 2005;Yeomans and Baptista, 1997;Yeomans et al, 2001) Striatum Striatal ACh increase associated with reward, possibly satiation (Imperato et al, 1993a, b;Mark et al, 1992;Pratt and Kelley, 2004;Zocchi and Pert, 1994).…”
Section: Overview Of Animal Models Of Addictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of equal interest, however, is the impact of the mACh receptor on cocaine-induced reward and administration. The rewarding effects of cocaine are mediated by M 5 receptors in the ventral tegmentum (Fink-Jensen et al, 2003;Thomsen et al, 2005;Yeomans et al, 2001) and M 5 -deficient rats show an attenuation of cocaine-induced conditioned place preference (Fink-Jensen et al, 2003). Several investigators have observed alterations in striatal mACh receptors after chronic cocaine administration (Lipton et al, 1995;Macedo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%